High-purity superfine aluminum oxide, preparation method thereof and lithium battery diaphragm
By using industrial aluminum hydroxide and Bomtestone to prepare high -purity ultra -fine aluminum oxide, the problem of complex and high cost of existing technology and high cost, high -efficiency high -purity ultra -fine aluminum oxide, suitable for lithium battery diaphragm coating layer.
Patent Information
- Application Number
- CN202411518353.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
AI Technical Summary
The preparation process of high-purity ultrafine alumina for existing lithium battery separators is complex, with high production costs and expensive products, which limits its wide application.
The use of industrial aluminum hydroxide and Bim as raw materials, prepare high -purity ultra -fine aluminum oxide through steps such as mixing, burning and grinding, and use composite crystal activation agent to regulate the crystal appearance and grain size of the products of the roasted products to reduce production costs Essence
The low-cost and efficient preparation of high-purity ultra-fine aluminum oxide is realized. The product has uniform grain size, narrow particle size distribution, and high alpha-phase conversion rate, which is suitable for lithium battery diaphragm coating.
Smart Images

Figure CN119370875A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium battery separator materials, and in particular to a high-purity ultrafine alumina and a preparation method thereof, and a lithium battery separator. Background Art
[0002] In recent years, the development momentum of new energy vehicles has been strong, and the global power battery industry has flourished. However, from the perspective of pure electric vehicle applications, their energy density still needs to be greatly improved, and they must also have a high degree of safety. The improvement of battery performance requires the upgrading of battery materials, the improvement of process levels, and the guarantee of high-level production equipment. Among them, the use of new materials is a necessary condition to achieve this goal. As one of the four major raw materials of power batteries, the performance of the diaphragm not only determines the interface structure and internal resistance of the battery, but also directly affects the battery's capacity, cycle, and safety performance.
[0003] Lithium batteries have outstanding advantages. Benefiting from the rapid growth of power batteries, the demand for lithium battery separators is also rising. The market demand for alumina used for lithium battery separator coating will increase significantly. α-alumina is an inorganic oxide with high thermal stability and chemical inertness. It is an industrial raw material with the characteristics of easy access and is a good choice for lithium battery separator coating. Existing α-alumina used in lithium battery separators mostly uses high-purity ultrafine alumina, but there are problems such as complex process, high production cost, and high product price, which are increasingly limited in practical applications. Summary of the invention
[0004] The present application provides a high-purity ultrafine alumina and a preparation method thereof, and a lithium battery separator to solve the following technical problems: providing a new preparation method of high-purity ultrafine alumina.
[0005] In a first aspect, the present application provides a method for preparing high-purity ultrafine alumina, the method comprising:
[0006] Mixing industrial aluminum hydroxide, boehmite and a composite crystal activator to obtain a mixed material;
[0007] calcining the mixture under a set temperature to obtain α-alumina powder;
[0008] The α-alumina powder is ground to obtain high-purity ultrafine alumina.
[0009] Optionally, the set temperature is 1250°C to 1350°C.
[0010] Optionally, the composite crystal activator includes at least two of the following: ammonium chloride, boric acid, and aluminum fluoride.
[0011] Optionally, the weight of the composite crystal activator is 0.1% to 1% of the weight of the industrial aluminum hydroxide.
[0012] Optionally, the grinding is performed using a grinding aid, which includes water.
[0013] Optionally, the weight ratio of the α-alumina powder to the grinding aid is (20-50):(50-80).
[0014] Optionally, the method further includes:
[0015] The high-purity ultrafine alumina is spray-dried to obtain the target high-purity ultrafine alumina.
[0016] Optionally, the high-purity ultrafine alumina meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is ≥95%, and the alumina content is ≥99.9%;
[0017] Alumina particle size and distribution: D 50 0.5μm~1.0μm and meets: D 10 ≥0.4μm, D 90 ≤2.5μm,
[0018] D 99 ≤4μm.
[0019] In a second aspect, the present application provides a high-purity ultrafine alumina, which is prepared by any method described in the first aspect.
[0020] In a third aspect, the present application provides a lithium battery separator, comprising a lithium battery separator substrate and a coating attached to at least a portion of the surface of the lithium battery separator substrate, wherein the raw material of the coating comprises the high-purity ultrafine alumina described in any one of the second aspects.
[0021] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0022] The preparation method of the high-purity ultrafine alumina provided in an embodiment of the present application comprises: mixing industrial aluminum hydroxide, boehmite and a composite crystal activator to obtain a mixed material; calcining the mixed material under a set temperature to obtain α-alumina powder; and grinding the α-alumina powder to obtain high-purity ultrafine alumina. Industrial aluminum hydroxide and boehmite are used as raw materials with low cost. Boehmite with low particle size can promote the regulation of the crystal morphology and grain size of the calcined product in coordination with industrial aluminum hydroxide, so that the mixed material can quickly obtain α-phase aluminum oxide powder in the subsequent calcination process, and reduce the temperature of subsequent calcination to a certain extent, saving energy consumption; under the condition of set temperature, the mixed material is calcined to obtain α-alumina powder with target grain size and high α-phase conversion rate; the composite crystal activator plays a positive role in the crystal morphology, grain size and purity of the α-alumina powder during the calcination process; the α-alumina powder is ground to further effectively regulate the particle size distribution of aluminum oxide to obtain high-purity ultrafine aluminum oxide. Therefore, the method has the advantages of simple process, low production cost, high production efficiency, uniform product grains, high purity ultrafine, narrow particle size distribution and high α-phase conversion rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0025] Figure 1 A schematic flow chart of a method for preparing high-purity ultrafine alumina provided in an embodiment of the present application. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0027] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0028] In the present application, unless otherwise specified, the directional words used, such as "above" and "below", refer specifically to the directions of the drawings in the accompanying drawings. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple, respectively. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula according to the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond one by one to the proportional numbers in the proportional formula according to the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.
[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0030] In a first aspect, the present application provides a method for preparing high-purity ultrafine alumina. Figure 1 A schematic diagram of a process for preparing a high-purity ultrafine alumina provided in the embodiment of the present application; see Figure 1 , the method comprising:
[0031] S1. Mixing industrial aluminum hydroxide, boehmite and a composite crystal activator to obtain a mixed material;
[0032] In some embodiments, the composite crystal activator includes at least two of the following: ammonium chloride, boric acid, and aluminum fluoride.
[0033] In the embodiments of the present application, a composite crystal activator is used to regulate the crystal morphology and grain size of the α-alumina powder obtained by calcination, and to effectively remove soluble impurities such as sodium oxide in the raw material, thereby improving the purity of the α-alumina powder. Compared with a single crystal activator, the composite crystal activator can have a certain positive effect on the purity, grain morphology and grain size of the α-alumina powder. The composite crystal activator can include a combination of two or three of the following: ammonium chloride, boric acid, and aluminum fluoride. Industrial aluminum hydroxide has a wide range of sources, is easily available, has low production costs, and has a particle size of D 50 It can be 30μm to 65μm. In the process of preparing alumina, boehmite is added to the raw material on the basis of industrial aluminum hydroxide. The production cost of boehmite is relatively low. Boehmite has the advantages of morphological controllability and plate-like structure characteristics in structure, and has high thermal stability and chemical properties. The particle size D of boehmite 50 It can be 1.2μm to 3.0μm, with uniform particle size distribution, which is conducive to the particle size control of the target product. Therefore, industrial aluminum hydroxide has a wide range of sources and relatively low costs. Through certain process treatments, particles with different particle size distributions can be obtained, while boehmite has a specific plate-like structure and a relatively uniform particle size. The coordinated use of the two can comprehensively control the particle size and morphology of alumina, and to a certain extent improve the thermal stability and chemical stability of the target product, while taking into account the production cost; the coordinated use of industrial aluminum hydroxide and boehmite reduces the temperature and time of subsequent calcination and saves energy consumption.
[0034] In some embodiments, the weight of the composite crystal activator is 0.1% to 1% of the weight of the industrial aluminum hydroxide.
[0035] In an embodiment of the present application, the weight of the composite crystal activator can be 0.1% to 1% of the weight of industrial aluminum hydroxide, while taking into account the regulation of the grain morphology and grain size of the α-alumina powder obtained by calcination, that is, taking into account the appropriate alumina grain size and a higher alumina α phase conversion rate. Exemplarily, the weight of the above-mentioned composite crystal activator can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. of the weight of industrial aluminum hydroxide. Further, the weight of the composite crystal activator can be 0.5% to 1% of the weight of industrial aluminum hydroxide.
[0036] S2. calcining the mixture at a set temperature to obtain α-alumina powder;
[0037] In some embodiments, the set temperature is 1250°C to 1350°C.
[0038] In the embodiments of the present application, "set temperature" refers to the calcination temperature, which can be 1250°C to 1350°C, while taking into account the regulation of the grain morphology and grain size of the α-alumina powder obtained by calcination, that is, taking into account the appropriate alumina grain size and a higher alumina α phase conversion rate. Exemplarily, the above calcination temperature can be 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C, 1310°C, 1320°C, 1330°C, 1340°C, 1350°C, etc. Correspondingly, the calcination time can be 2h to 5h.
[0039] S3, grinding the α-alumina powder to obtain high-purity ultrafine alumina.
[0040] In some embodiments, the grinding is performed using a grinding aid, the grinding aid comprising water.
[0041] In some embodiments, the weight ratio of the α-alumina powder to the grinding aid is (20-50):(50-80).
[0042] In an embodiment of the present application, α-alumina powder is ground to further effectively regulate the particle size distribution of alumina to obtain high-purity ultrafine alumina. The grinding is carried out using a grinding aid, which may include water, and the weight ratio of α-alumina powder to the grinding aid may be (20-50): (50-80), thereby improving the grinding efficiency while controlling the cost. Exemplarily, the weight ratio of the above-mentioned α-alumina powder to the grinding aid may be 20:80, 30:70, 40:60, 45:55, 50:50, etc. Exemplarily, a sand mill may be used for the grinding, and the speed may be set to 2000rpm to 3000rpm.
[0043] In some embodiments, the method further comprises:
[0044] S4. Spray-drying the high-purity ultrafine alumina to obtain target high-purity ultrafine alumina.
[0045] In the embodiments of the present application, high-purity ultrafine alumina can be spray-dried to dry the high-purity ultrafine alumina to a suitable moisture content and improve the dispersibility of the high-purity ultrafine alumina. The spray drying temperature can be 200°C to 250°C.
[0046] In some embodiments, the high-purity ultrafine alumina meets the following indicators: the alumina crystal form is α-type, the α-phase transition
[0047] The conversion rate is ≥95%, and the alumina content is ≥99.9%;
[0048] Alumina particle size and distribution: D 500.5μm~1.0μm and meets: D 10 ≥0.4μm, D 90 ≤2.5μm,
[0049] D 99 ≤4μm.
[0050] In the examples of the present application, the above-mentioned method for preparing high-purity ultrafine alumina is used to obtain high-purity ultrafine alumina with uniform grains, high purity and ultrafine, narrow particle size distribution and high α-phase conversion rate.
[0051] In summary, the present application provides a method for preparing high-purity ultrafine alumina, and the advantages are as follows:
[0052] 1. Raw material advantages: Industrial aluminum hydroxide and boehmite are selected not only because of their relatively low cost, but more importantly, they each have unique physical and chemical properties. Industrial aluminum hydroxide, as the main alumina precursor, provides a rich source of aluminum. Boehmite, due to its low particle size and specific crystal structure, can play a synergistic role in the calcination process, promote the rapid growth and phase change of alumina crystals, and help to form a uniform grain size and morphology.
[0053] 2. Optimization of the calcination process: On the one hand, by precisely controlling the calcination temperature, it is possible to ensure that the mixed material undergoes a phase change reaction under optimal conditions to generate α-alumina powder with a target grain size. In addition, the addition of boehmite may reduce the required calcination temperature to a certain extent, thereby saving energy consumption and reducing production costs. On the other hand, the selection of a composite crystal activator as an additive plays a vital role in the calcination process. It not only promotes the formation of α-alumina and improves the α-phase conversion rate, but also optimizes the crystal morphology and grain size, so that the final product has a higher purity and a narrower particle size distribution. The specific composition and mechanism of action of the composite crystal activator may involve a variety of complex processes such as catalyst effect and surface modification.
[0054] 3. Contribution of the grinding process: Although the α-alumina powder obtained after calcination has a certain degree of fineness and purity, through further grinding treatment, its particle size distribution can be more accurately controlled to make the product reach the ultra-fine level. This is especially important for applications that require high specific surface area or special particle size distribution.
[0055] Therefore, the preparation method of high-purity ultrafine alumina shows significant advantages in raw material selection, process optimization and product quality control, and has broad application prospects and market potential.
[0056] In a second aspect, the present application provides a high-purity ultrafine alumina, which is prepared by any method described in the first aspect.
[0057] The high-purity ultrafine alumina is realized based on the preparation method of the high-purity ultrafine alumina mentioned above. The specific steps of the preparation method of the high-purity ultrafine alumina can refer to the above embodiment. Since the high-purity ultrafine alumina adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be described one by one here.
[0058] In a third aspect, the present application provides a lithium battery separator, comprising a lithium battery separator substrate and a coating attached to at least a portion of the surface of the lithium battery separator substrate, wherein the raw material of the coating comprises the high-purity ultrafine alumina described in any one of the second aspects.
[0059] In the embodiments of the present application, the above-mentioned high-purity ultrafine alumina is α-alumina. α-alumina is an inorganic oxide with high thermal stability and chemical inertness. It is an industrial raw material and has the characteristics of being easy to obtain. It is a good choice for lithium battery diaphragm coating. The α-alumina coating has excellent high temperature resistance and can form a layer of high temperature resistant ceramic coating on the surface of the diaphragm, thereby greatly improving the high temperature resistance and safety of the lithium battery. At the same time, alumina has high mechanical strength and can greatly improve the puncture resistance of the diaphragm, thereby further improving the safety of the diaphragm. The α-alumina coating can neutralize the free HF in the electrolyte, improve the acid resistance of the battery, and increase the service life of the battery. The alumina ceramic particles coated on the surface of the lithium battery diaphragm have a large number of lyophilic groups such as -OH distributed on the surface, have good liquid absorption and liquid retention capabilities, and can effectively improve the wettability of the diaphragm.
[0060] The lithium battery separator is realized based on the above-mentioned high-purity ultrafine alumina. The specific preparation steps of the high-purity ultrafine alumina can refer to the above-mentioned embodiments. Since the lithium battery separator adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0061] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.
[0062] Example 1
[0063] At 5m 3In a plastic stirring tank, 1.3 tons (T) of industrial aluminum hydroxide, 0.2T of boehmite and a composite crystal activator (the weight of the composite crystal activator is 0.5% of the weight of industrial aluminum hydroxide, 0.2% ammonium chloride + 0.3 aluminum fluoride) are added and mixed evenly, and calcined in a tunnel kiln at a calcination temperature of 1300°C for 3 hours to obtain α-alumina with submicron grains; 1.5T of α-alumina is added to 2.8T of pure water, stirred evenly, and then ground with a sand mill for 5 hours to D 50 The ground slurry is spray-dried at 240°C to obtain the target high-purity ultrafine alumina.
[0064] The target high-purity ultrafine alumina prepared in Example 1 meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is 95.1%, the alumina content is 99.97%, and the alumina particle size and distribution are: D 50 is 0.851μm and satisfies: D 10 0.533 μm 90 1.675 μm D 99 It is 3.061μm.
[0065] Example 2
[0066] At 5m 3 In a plastic stirring tank, 1.1T industrial aluminum hydroxide, 0.4T boehmite and 0.5% composite crystal activator (the weight of the composite crystal activator is 0.5% of the weight of industrial aluminum hydroxide, 0.3% ammonium chloride + 0.2% boric acid) are added and mixed evenly, and calcined in a tunnel kiln at a calcination temperature of 1340°C for 2 hours to obtain α-alumina with submicron grains; 1T α-alumina is added to 2.2T pure water, stirred evenly, and then ground with a sand mill for 6 hours to D 50 The particle size of the alumina was 0.82 μm, and the ground slurry was spray dried at 240°C to obtain the target high-purity ultrafine alumina.
[0067] The target high-purity ultrafine alumina prepared in Example 2 meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is 95.3%, the alumina content is 99.96%, and the alumina particle size and distribution are: D 50 is 0.819μm and satisfies: D 10 0.524 μm, D 90 1.707μm, D 99 It is 2.920μm.
[0068] Example 3
[0069] At 5m 3In a plastic stirring tank, 1.1T of industrial aluminum hydroxide, 0.4T of boehmite and 0.9% of a composite crystal activator (the weight of the composite crystal activator is 0.9% of the weight of the industrial aluminum hydroxide, 0.5% ammonium chloride + 0.2% boric acid + 0.2% aluminum fluoride) are added and mixed evenly, and calcined in a tunnel kiln at a calcination temperature of 1280°C for 4 hours to obtain α-alumina with submicron grains; 1T of α-alumina is added to 2.3T of pure water, stirred evenly, and then ground with a sand mill for 7 hours to D 50 The particle size of the alumina was 0.78 μm, and the ground slurry was spray dried at 230°C to obtain the target high-purity ultrafine alumina.
[0070] The target high-purity ultrafine alumina prepared in Example 3 meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is 95.5%, the alumina content is 99.97%, and the alumina particle size and distribution are: D 50 is 0.77μm and satisfies: D 10 0.515μm, D 90 1.614 μm, D 99 It is 2.870μm.
[0071] Example 4
[0072] At 5m 3 In a plastic stirring tank, 1.0T industrial aluminum hydroxide, 0.5T boehmite and 0.9% composite crystal activator (the weight of the composite crystal activator is 0.9% of the weight of industrial aluminum hydroxide, 0.5% ammonium chloride + 0.2% boric acid + 0.2% aluminum fluoride) are added and mixed evenly, and calcined in a tunnel kiln at a calcination temperature of 1250°C for 5 hours to obtain α-alumina with submicron grains; 1.5T α-alumina is added to 2.25T pure water, stirred evenly, and ground with a sand mill for 8h to D 50 The particle size of the alumina was 0.698 μm, and the ground slurry was spray-dried at 230° C. to obtain the target high-purity ultrafine alumina.
[0073] The target high-purity ultrafine alumina prepared in Example 4 meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is 95.2%, the alumina content is 99.97%, and the alumina particle size and distribution are: D 50 is 0.676μm and satisfies: D 10 0.466μm, D 90 1.253 μm, D 99 It is 2.091μm.
[0074] Comparative Example 1
[0075] At 5m 3In a plastic stirring tank, 1.3T industrial aluminum hydroxide, 0.2T boehmite and a single crystal activator (the weight of the single crystal activator is 0.5% of the weight of the industrial aluminum hydroxide, 0.5% ammonium chloride) are added and mixed evenly, and calcined in a tunnel kiln at a calcination temperature of 1300°C to obtain α-alumina with submicron grains; 1.5T α-alumina is added to 2.8T pure water, stirred evenly, and then ground with a sand mill for 5h to D 50 The particle size of the alumina was 0.494 μm. The ground slurry was spray dried at 240°C to obtain the target high-purity ultrafine alumina.
[0076] The target high-purity ultrafine alumina prepared in Comparative Example 1 meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is 94.5%, the alumina content is 99.92%, and the alumina particle size and distribution are: D 50 is 0.494μm and satisfies: D 10 0.368μm, D 90 0.698μm, D 99 It is 0.861μm.
[0077] Comparative Example 2
[0078] At 5m 3 In a plastic stirring tank, 1.5T of industrial aluminum hydroxide and a composite crystal activator (the weight of the composite crystal activator is 0.5% of the weight of industrial aluminum hydroxide, 0.2% ammonium chloride + 0.3 aluminum fluoride) are added and mixed evenly, and calcined in a tunnel kiln at a calcination temperature of 1300°C to obtain α-alumina with submicron grains; 1.5T α-alumina is added to 2.8T pure water, stirred evenly, and then ground with a sand mill for 5h to D 50 The particle size of the alumina was 0.489 μm. The ground slurry was spray dried at 240°C to obtain the target high-purity ultrafine alumina.
[0079] The target high-purity ultrafine alumina prepared in Comparative Example 2 meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is 92.7%, the alumina content is 99.85%, and the alumina particle size and distribution are: D 50 is 0.489μm and satisfies: D 10 0.363μm, D 90 0.701μm, D 99 It is 0.864μm.
[0080] Comparative Example 3
[0081] At 5m 3In a plastic stirring tank, 1.3T industrial aluminum hydroxide, 0.2T boehmite and a composite crystal activator (the weight of the composite crystal activator is 0.5% of the weight of industrial aluminum hydroxide, 0.2% ammonium chloride + 0.3 aluminum fluoride) are added and mixed evenly, and calcined in a tunnel kiln at a calcination temperature of 1400°C to obtain α-alumina with submicron grains; 1.5T α-alumina is added to 2.8T pure water, stirred evenly, and then ground with a sand mill for 5h to D 50 The particle size of the alumina was 1.191 μm; the ground slurry was spray dried at 240°C to obtain the target high-purity ultrafine alumina.
[0082] The target high-purity ultrafine alumina prepared in Comparative Example 3 meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is 95.5%, the alumina content is 99.95%, and the alumina particle size and distribution are: D 50 is 1.191μm and satisfies: D 10 0.627 μm, D 90 2.581μm, D 99 It is 3.789μm.
[0083] In the examples of the present application, it can be seen from the above examples 1 to 4 that the high-purity ultrafine alumina prepared in the examples of the present application meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is ≥95%, and the alumina content is ≥99.9%; the alumina particle size and distribution: D 50 0.5μm~1.0μm and meets: D 10 ≥0.4μm, D 90 ≤2.5μm, D 99 ≤4μm, which can fully meet the requirements of being used as a raw material for lithium battery separator coating. Comparative Examples 1 to 3 are set on the basis of Example 1. In Comparative Example 1, only a single crystal activator is used, resulting in a decrease in the α phase conversion rate to <95%, a decrease in the grain size, and alumina D 50 <0.5μm; In Comparative Example 2, only industrial aluminum hydroxide was used, resulting in the α phase conversion rate being reduced to <95%, the aluminum oxide content being reduced to <99.9%, the grain size being smaller, and the aluminum oxide D 50 <0.5μm; In comparative example 3, the calcination temperature is too high, resulting in a larger grain size, and the aluminum oxide D 50 >1μm.
[0084] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:
[0085] (1) The high-purity ultrafine alumina for lithium battery separator coating provided in the embodiments of the present application has a suitable particle size and distribution, low impurity content, and high α-phase conversion rate;
[0086] (2) Compared with the prior art, the embodiment of the present application uses industrial aluminum hydroxide and boehmite as raw materials, which has a lower cost. By adding a seed crystal activator, soluble impurities such as sodium oxide in the raw materials can be effectively removed, thereby reducing the impurity content of aluminum oxide for lithium ion diaphragm coating; calcination can not only prevent the growth of original crystals, but also obtain a higher α-phase conversion rate; ultrafine grinding can effectively control the particle size distribution of the product and avoid over-grinding of α-alumina; the slurry after grinding is spray-dried, and the obtained ultrafine α-alumina has good dispersibility;
[0087] (3) The method for preparing high-purity ultrafine alumina for lithium battery diaphragm coating provided in the embodiment of the present application has a simple process, low production cost and high production efficiency; the corresponding product has uniform grains, high purity and ultrafine, narrow particle size distribution and high α-phase conversion rate.
[0088] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing high-purity ultrafine alumina, characterized in that: The method comprises: Mixing industrial aluminum hydroxide, boehmite and a composite crystal activator to obtain a mixed material; calcining the mixture under a set temperature to obtain α-alumina powder; The α-alumina powder is ground to obtain high-purity ultrafine alumina.
2. The method according to claim 1, characterized in that The set temperature is 1250°C to 1350°C.
3. The method according to claim 1, characterized in that The composite crystal activator comprises at least two of the following: ammonium chloride, boric acid, and aluminum fluoride.
4. The method according to claim 1 or 3, characterized in that: The weight of the composite crystal activator is 0.1% to 1% of the weight of the industrial aluminum hydroxide.
5. The method according to claim 1, characterized in that The grinding is performed using a grinding aid, which includes water.
6. The method according to claim 5, characterized in that The weight ratio of the α-alumina powder to the grinding aid is (20-50):(50-80).
7. The method according to claim 1, characterized in that The method further comprises: The high-purity ultrafine alumina is spray-dried to obtain the target high-purity ultrafine alumina.
8. The method according to claim 1, characterized in that The high-purity ultrafine alumina meets the following indicators: the alumina crystal form is α-type, the α-phase conversion rate is ≥95%, and the alumina content is ≥99.9%; Alumina particle size and distribution: D 50 0.5μm~1.0μm and meets: D 10 ≥0.4μm, D 90 ≤2.5μm, D 99 ≤4μm.
9. A high-purity ultrafine alumina, characterized in that: The high-purity ultrafine alumina is prepared by the method described in any one of claims 1 to 8.
10. A lithium battery separator, characterized in that: The lithium battery separator comprises a lithium battery separator substrate and a coating adhered to at least a portion of the surface of the lithium battery separator substrate, and the raw material of the coating comprises the high-purity ultrafine alumina described in claim 9.
Citation Information
Cited By
High-purity single crystal alpha-alumina and preparation method thereof
CN121020624A